New pyridine based liquid crystalline esters with different terminal chains - Karanlik, Gurkan; Ocak, Hale; Eran, Belkiz Bilgin (ELSEVIER, 2019)
The synthesis, structural and mesomorphic characterization of new pyridine-based methyl esters carrying a n-alkoxy chain or 3,7-Dimethyloctyloxy branched group at terminal have been presented. The liquid crystalline properties of the new pyridine-based calamitic molecules have been investigated by polarized optical microscopy and differential scanning calorimetry. New compounds exhibit enantiotropic smectic A mesophase at a variable mesomorphic range depending on alkoxy chain length and branching at terminal. The presence of a branched terminal group in chiral or racemic form gives rise to a sharply increase in mesomorphic range as well as decrease in crystallization points by preserving mesophase type. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Liquid crystal; Calamitic molecule; Pyridine-based methyl esters; Smectic mesophase; MESOMORPHIC PROPERTIES; ELECTRONIC-PROPERTIES; SERIES; Chemistry